Factors influencing rehabilitation in patients with head and neck cancer - Hočevar-Boltežar, Irena (Radiology and oncology (Ljubljana), 2000)
Purpose. The purpose of the prospective study was to identify the factors adversely influencing the post-treatment rehabilitation in patients with head and neck cancer. Patients and methods. One hundred and ten patients with oral cavity, pharyngeal and laryngeal cancer were examined before surgical treatment in order to find unfavorable factors: hearing loss, defective teeth,impaired pulmonary function, and speech disorders. The patients evaluated the success of their rehabilitation 12 months after the treatment. The influence of possible unfavorable factors, tumor site, and type of surgeryon speech, swallowing and reintegration competence was determinated. Results. The site of the tumor and the type of surgery did not influence the quality of rehabilitation in general. Defective teeth influenced the ability of swallowing but not the speech. Hearing loss impaired the patient's reintegration in their home environment. Impaired pulmonary function did not affect patient's speech. Speech was the poorest in laryngectomized patients. However, about two thirds of the patients were satisfied with their capabilityof speech, swallowing and their rehabilitation in general. Conclusions. Early identification of unfavorable factors, and individually planned rehabilitation can ensure a suitable quality of life for patients thathave undergone surgery for head and neck cancer.
Keywords: dejavniki; Dental health surveys; glava; grlo; Head and neck neoplasms; Hearing disorders; Lung; Neoplasm staging; Radiography; rak (medicina); rehabilitacija; Rehabilitation; Speech disorders; Spirometry